2020
DOI: 10.2147/opth.s271923
|View full text |Cite
|
Sign up to set email alerts
|

<p>Excisional Goniotomy in Latino Patients with Open-Angle Glaucoma: Outcomes Through 24 Months</p>

Abstract: Purpose To characterize the efficacy of combined phacoemulsification and excisional goniotomy with the Kahook Dual Blade (KDB-phaco) in eyes of Latino adults with cataract and open-angle glaucoma (OAG). Methods Health records of consecutive Latino patients undergoing KDB-phaco were retrospectively reviewed. Intraocular pressure (IOP) and IOP-lowering medication use were recorded at baseline and each postoperative visit through up to 24 months. Primary outcomes were redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Using multiple regression analysis, preoperative IOP was the significant indicator with the highest standard β value for predicting postoperative IOP ( Table 4 ). A lower IOP-reducing magnitude in the lower preoperative IOP group than in the higher IOP group was reported after other goniotomy procedures with Kahook dual blade (KDB) [ 11 , 12 ] and trabectome [ 13 ]. Figure 2 shows the correlation between preoperative IOP and 12 months %IOP reduction after various goniotomy/LOT surgeries including µLOT, KDB, gonioscopy-assisted transluminal trabeculotomy (GATT), and trabectome in subject groups including POAG (data and references used for generation of this figure are shown in Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using multiple regression analysis, preoperative IOP was the significant indicator with the highest standard β value for predicting postoperative IOP ( Table 4 ). A lower IOP-reducing magnitude in the lower preoperative IOP group than in the higher IOP group was reported after other goniotomy procedures with Kahook dual blade (KDB) [ 11 , 12 ] and trabectome [ 13 ]. Figure 2 shows the correlation between preoperative IOP and 12 months %IOP reduction after various goniotomy/LOT surgeries including µLOT, KDB, gonioscopy-assisted transluminal trabeculotomy (GATT), and trabectome in subject groups including POAG (data and references used for generation of this figure are shown in Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, various factors that possibly associate with the surgical efficacy of LOT/goniotomy surgeries were reported; the factors assessed included age [ 10 ], preoperative IOP level [ 11 , 12 , 13 ], degree of angle opening [ 14 ], glaucoma severity [ 15 , 16 , 17 , 18 ], and simultaneous cataract surgery [ 10 , 19 , 20 , 21 ]. In case series of µLOT, by using multiple regression analyses, we have previously reported that older age, steroid-induced glaucoma, developmental glaucoma, and the absence of postoperative complications were associated with lower final IOP; exfoliation glaucoma, other types of glaucoma, and higher preoperative IOP were associated with higher final IOP [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of reports associated with MIGS have identified the risk factors and prognosis; however, there are still problems to be solved. A vexing complication in procedures targeting the TM tissue is IOP spikes, and the incidence of IOP spikes in ab interno trabeculotomy using a KDB (KDB trabeculotomy) ranges from 7.7% to 18.2% [6][7][8][9]. Uncontrolled high IOP levels may worsen visual field defects; one report showed that 14.3% (6/42) of eyes required additional procedures for IOP reduction within three months after KDB trabeculotomy [10].…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 IOP lowering at POM12 in the KDB group was lower than those of other studies, which had POM12 reductions ranging from 2.4–6.5 mm Hg. 17 , 21 23 …”
Section: Discussionmentioning
confidence: 99%
“… 15 At a 2-year follow-up, KDB combined with CE/IOL has been shown to decrease IOP by 4.3–7.2 mm Hg and decrease glaucoma medications by 0.7. 16 , 17 Only a few studies have examined outcomes of trainee-performed KDB, 18 , 19 and to our knowledge, none have characterized trainee outcomes with ECP. No studies have directly compared KDB and ECP on a large scale.…”
Section: Introductionmentioning
confidence: 99%